Effect of epinephrine on the absorption of lidocaine following application to the oral mucosa in rats - Rui Sasaki; Katsuhisa Sunada (BMC, 2021)
Abstract Background We investigated the role of epinephrine in prolonging the localization of lidocaine on the oral mucosa and inhibiting its absorption in the blood of rats. Methods We used 7-8-week-old pathogen-free Wistar male rats (n = 128) for our study. We divided them into the control group administered with 14C-labeled lidocaine hydrochloride gel only and the study group administered with 14C-labeled lidocaine hydrochloride gel with epinephrine. The medications were administered in the palatal mucosa of the rats. The amount of mucosa, palatine bone, and serum lidocaine was measured by radioactivity using a liquid scintillation counter and was observed using autoradiograms. Results Initially, there was no significant difference in the lidocaine levels between the lidocaine and lidocaine with epinephrine groups in the palatal mucosa (751.9 ± 133.8 vs. 669.8 ± 101.6 ng/mg [2 min]). After 4 min, the values were significantly lower in the lidocaine with epinephrine group (1040.0 ± 142.8 vs. 701.2 ± 109.0 ng/mg [20 min]). After 40 min, the lidocaine level became significantly higher in the lidocaine with epinephrine group (586.8 ± 112.4 vs. 1131.3 ± 155.2 ng/mg [40 min]). Similar results were observed in the palatine bone and serum. Conclusion Epinephrine prolonged the localization of lidocaine applied to the mucosa and inhibited its absorption into the bloodstream of rats. Clinical studies are required to evaluate the use of epinephrine-containing topical anesthetics on the oral mucosa.